Genetic Ablation of the Mitochondrial Calcium Uniporter (MCU) Does not Impair T Cell-Mediated Immunity In Vivo - Wu, Hao; Brand, Benjamin; Eckstein, Miriam; Hochrein, Sophia M.; Shumanska, Magdalena; Dudek, Jan; Nickel, Alexander; Maack, Christoph; Bogeski, Ivan; Vaeth, Martin (Frontiers in Pharmacology, 2021)
T cell activation and differentiation is associated with metabolic reprogramming to cope with the increased bioenergetic demand and to provide metabolic intermediates for the biosynthesis of building blocks. Antigen receptor stimulation not only promotes the metabolic switch of lymphocytes but also triggers the uptake of calcium (Ca2+) from the cytosol into the mitochondrial matrix. Whether mitochondrial Ca2+ influx through the mitochondrial Ca2+ uniporter (MCU) controls T cell metabolism and effector function remained, however, enigmatic. Using mice with T cell-specific deletion of MCU, we here show that genetic inactivation of mitochondrial Ca2+ uptake increased cytosolic Ca2+ levels following antigen receptor stimulation and store-operated Ca2+ entry (SOCE). However, ablation of MCU and the elevation of cytosolic Ca2+ did not affect mitochondrial respiration, differentiation and effector function of inflammatory and regulatory T cell subsets in vitro and in animal models of T cell-mediated autoimmunity and chronic viral infection. These data suggest that MCU-mediated mitochondrial Ca2+ uptake is largely dispensable for murine T cells. Our study has also important technical implications. Previous studies relied mostly on pharmacological inhibition or transient knockdown of mitochondrial Ca2+ uptake, but our results using mice with genetic deletion of MCU did not recapitulate these findings. The discrepancy of our study to previous reports hint at compensatory mechanisms in MCU-deficient mice and/or off-target effects of current MCU inhibitors.